2016
DOI: 10.1016/j.jcm.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Multimodal Interventions With and Without Whole Body Vibration Therapy Plus Traction on Pain and Disability in Patients With Nonspecific Chronic Low Back Pain

Abstract: The results of this preliminary study suggest that NPS and ODI scores statistically improved for both NSCLBP groups receiving multimodal care. However, the group that included WBV therapy plus traction in combination with multimodal care had greater clinical results. This study had several limitations making it difficult to generalize the results from this study sample to the entire population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 72 publications
(80 reference statements)
1
18
0
Order By: Relevance
“…We understand that tissue healing is an intricate process that is regulated by circulation. Recent research supports that passive vibration can increase circulation and has plausible effect on chronic back pain [8][9][10]. Looking at the athletes and not only athletes many subjects develop excessive connective tissue fibrosis or poorly organized scar tissue in and around joints, muscles, tendons, ligaments, myofascial planes as a result of acute trauma, recurrent microtrauma, immobilization, or as a complication of surgical intervention.…”
Section: Physiological Benefits Of Vibrotherapymentioning
confidence: 99%
“…We understand that tissue healing is an intricate process that is regulated by circulation. Recent research supports that passive vibration can increase circulation and has plausible effect on chronic back pain [8][9][10]. Looking at the athletes and not only athletes many subjects develop excessive connective tissue fibrosis or poorly organized scar tissue in and around joints, muscles, tendons, ligaments, myofascial planes as a result of acute trauma, recurrent microtrauma, immobilization, or as a complication of surgical intervention.…”
Section: Physiological Benefits Of Vibrotherapymentioning
confidence: 99%
“…If one PSIS moves further forward, the test is positive for SIJ-dysfunction [ 37 ]. Manual therapeutic techniques 1.Vibrating traction of both legs : the patient is either lying on the back or face down, the GP takes hold of the legs above the ankle with both hands and pulls the legs vibrating simultaneously [ 37 , 38 ]. Vibrating traction was presented with a low frequency (20–40/min) at an angle between 20 and 40°.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, lumbar-abdominal muscle activation is also closely related to chronic low back pain (CLBP). Several clinical intervention studies reported that WBV training as an intervention method can reduce CLBP effectively and improve quality of life [16][17][18] . To our knowledge, no study researched the in uence of WBV training on patients with CLBP by lumbar-abdominal muscle activity.…”
Section: Introductionmentioning
confidence: 99%